PENGARUH JUMLAH OBYEK WISATA DAN JUMLAH KUNJUNGAN WISATAWAN TERHADAP PENYERAPAN TENAGA KERJA SEKTOR PARIWISATA PER PROVINSI DI INDONESIA - Made Sukaarnawa, I Gusti; Suwita Yanti, Ayu; Astrama, I Made; Darsana, I Made (Berajah Journal, 2024)
Tourism is a driver of the world economy that is proven to be able to contribute to the prosperity of a country. This sector can also be reached by people from various groups, so it is labor-intensive oriented and should be able to absorb a higher workforce compared to other sectors. The aim of this research is to determine and analyze the influence of the number of tourist attractions and the number of tourist visits on employment in the tourism sector per province in Indonesia. This research was designed as associative quantitative research. The population in this study is all 34 provinces in Indonesia. The sampling technique uses saturated sampling, so that the number of samples in this study is the same as the population. Data collection techniques through documentation studies obtained from data from the Indonesian Provincial Central Statistics Agency. The collected data will be analyzed using multiple linear regression analysis. The research results show that the number of tourist attractions and the number of tourist visits have a significant effect on employment in the tourism sector. This shows that if there are more tourist attractions and tourist visits in a province in Indonesia, then more workers will be absorbed in that area.